GAMBARAN TINGKAT LITERASI KESEHATAN MENTAL PADA PESERTA DIDIK SEKOLAH MENENGAH PERTAMA - HANDAYANI, RISKA; WAHYUNI, EKA; MARJO, HAPPY KARLINA (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2021)
Mental health is an important component that is closely related to social life, productivity, peace and stability in the environment, contributing to sosial life and economic development in Indonesian society. Mental health literacy is knowledge and beliefs about mental disorders that help to recognize, manage and prevent a personâ€™s mental disorder. Mental helath literacy is also knowledge related to actions to provide mental helath benefits to individuals and others. Mental helath literacy is the ability to gain knowledge or information about mental health for adolescents, understand and can maintain good mental health. Mental health literacy includes the ability to recognize specific mental health disorders, knowing how to seek mental health information, knowledge of risks and causes of health disorders. The aim of this study is to improve mental health literacy in students and meet the criteria for eligibility aspects. This study used Reeves Design Based Research model. The subjects in this study were students of class IX SMP Negeri 2 Kramatwatu. Collecting data using a questionnaire, in the form of an adaption instrument from a mental helath literacy question (MHLq). The results of this study indicate the level of mental health literacy in students obtained a value of 49% which is included in the moderate category.Â